EVALUATION OF BIO-PESTICIDES AGAINST RED COTTON BUG AND FRUIT BORER OF OKRA - SURAJ SARKAR,; SANDIP PATRA,; ARUNAVA SAMANTA, (The Bioscan, 2015)
Bio-pesticides were evaluated against red cotton bug (Dysdercus koenigii F.) and fruit borer (Helicoverpa armigera H.) in okra at Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal during pre-kharif season of 2013. The treatments viz. annonin 1% EC, karanjin 2% EC, Azadirachtin 1% EC, Metarrhizium anisopliae,Verticillium lecanii , Beauveria bassiana , Bacillus thuringiensis var Kurstaki, spinosad 45% SC and imidacloprid 17.8% SL were applied twice at 15 days interval at initiation of fruiting stage. Results revealed that mean population of red cotton bugs was lowest in imidacloprid treated plots (2.00 red cotton bugs/5 plants and 63.27% reduction) followed by azadirachtin with 2.87 red cotton bugs/5 plants and 47.90% reduction over control.After second spray, lowest mean fruit damage (1.05%) was recorded in spinosad treated plots followed by B.t. (7.88%). Highest marketable yield of okra was also recorded in spinosad treated plots (53.67 q/ha) followed by B.t. (42.26 q/ha), B. bassiana (39.28 q/ha) and azadirachtin (37.92 q/ha), respectively. Whereas, the yield obtained from untreated control plots was only 24.81 q/ha. Results revealed that imidacloprid and spinosad were very effective treatments against red cotton bug and fruit borer, respectively.